Settlement as a determinant for community's resilience to local economic development in Ghana - Vorodam, J. B. (2022)
Local Economic Development (LED) is the main anchor through which economic development is achieved by building entrepreneurial capacities and improving opportunities for economic growth and citizens' quality of life, especially in rural settlements. In Ghana, the implementation of LED is under the Ministry of Local Government, Decentralization and Rural Development (MLDGRD) through the Metropolitan, Municipal, and District Assemblies (MMDAs) at the local level. The implementation of LED contributes significantly to Ghana's economic growth, business creation, and employment generation. LED is therefore identified as essential to sustainable development and poverty reduction in rural settlements in Ghana. However, the challenges of poor implementation of the LED policy are financial constraints to implement LED activities at the local level, performance action of Public-Private Partnership (PPP) towards LED, and limited exploration of the sanitation value chain LED efforts at the local level. The poor capacity of small-medium micro enterprises (SMMEs) and smallholder farmers have often affected the successful implementation of LED activities at the local level. Hence, this paper seeks to identify the determinants for resilience in Local Economic Development in Ghana. The paper further provides an overview of the LED challenges in Ghana. Finally, this paper recommends appropriate theoretical frameworks that integrate the determinants for the resilience of Local Economic Development to address the identified challenges of LED, leading to poverty reduction in Ghana.